Trade liberalization and wage inequality: New insights from a dynamic trade model with heterogeneous firms and comparative advantage - Wolfgang Lechthaler; Mariya Mileva (Kiel Institute for the World Economy (IfW), 2014)
We develop a dynamic general equilibrium trade model with comparative advantage, heterogeneous firms, heterogeneous workers and endogenous firm entry to study wage inequality during the adjustment after trade liberalization. We find that trade liberalization increases wage inequality both in the short run and in the long run. In the short run, wage inequality is mainly driven by an increase in inter-sectoral wage inequality, while in the medium to long run, wage inequality is driven by an increase in the skill premium. Incorporating worker training in the model considerably reduces the effects of trade liberalization on wage inequality. The effects on wage inequality are much more adverse when trade liberalization is unilateral instead of bilateral or restricted to specific sectors instead of including all sectors.
Older version: http://hdl.handle.net/10419/88766
Keywords: E24; F11; F16; J62; 330; trade liberalization; wage inequality; adjustment dynamics